2020
DOI: 10.1093/mnras/staa2352
|View full text |Cite
|
Sign up to set email alerts
|

To β or not to β: can higher order Jeans analysis break the mass–anisotropy degeneracy in simulated dwarfs?

Abstract: We test a non-parametric higher-order Jeans analysis method, GravSphere, on 32 simulated dwarf galaxies comparable to classical Local Group dwarfs like Fornax. The galaxies are selected from the APOSTLE suite of cosmological hydrodynamics simulations with Cold Dark Matter (CDM) and Self-Interacting Dark Matter (SIDM) models, allowing us to investigate cusps and cores in density distributions. We find that, for CDM dwarfs, the recovered enclosed mass profiles have a bias of no more than 10 per cent, with a 50 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 106 publications
(145 reference statements)
2
51
0
Order By: Relevance
“…However, for data sets with ࣠1000 stars from both parameter sets -on par with the existing dwarf galaxy measurements -we cannot determine whether the underlying halo has an inner slope of γ = 0 or γ = 1 in a statistically significant manner, consistent with previous Jeans modelling-based results in the literature (e.g. Walker et al 2009;Read, Walker & Steger 2018;Genina et al 2020). We further note that, for the smaller sample sizes, the fact that the posterior γ distributions are unconstrained implies that the results are highly sensitive to the choice of priors on γ , and we therefore choose to present the full posterior distributions rather than to quote recovered median values or quantiles.…”
Section: Increase In Sample Sizesupporting
confidence: 75%
See 3 more Smart Citations
“…However, for data sets with ࣠1000 stars from both parameter sets -on par with the existing dwarf galaxy measurements -we cannot determine whether the underlying halo has an inner slope of γ = 0 or γ = 1 in a statistically significant manner, consistent with previous Jeans modelling-based results in the literature (e.g. Walker et al 2009;Read, Walker & Steger 2018;Genina et al 2020). We further note that, for the smaller sample sizes, the fact that the posterior γ distributions are unconstrained implies that the results are highly sensitive to the choice of priors on γ , and we therefore choose to present the full posterior distributions rather than to quote recovered median values or quantiles.…”
Section: Increase In Sample Sizesupporting
confidence: 75%
“…The degeneracy between the velocity anisotropy, β(r), and the enclosed mass profile, M(<r), is a known complication in Jeans modelling (e.g. Merrifield & Kent 1990;Wilkinson et al 2002;Lokas & Mamon 2003;De Lorenzi et al 2009;Read & Steger 2017;Genina et al 2020). It can be seen from equation (12) that β(r) and σ 2 r (r) are degenerate with each other, which, combined with equation ( 8), implies that β(r) is degenerate with M(<r).…”
Section: Jeans Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, it is non-trivial to infer the DM distribution from observations (e.g. Kowalczyk et al 2013;Harvey et al 2018;Oman et al 2019;Genina et al 2020;He et al 2020) and it is important to test how these difficulties impact the inferred SIDM cross-section when isothermal Jeans modelling is applied to observations. This was recently done in the context of galaxy cluster observations by Sagunski et al (2020), who found that the inferred cross-section from isothermal Jeans modelling using mock observations of simulated clusters was in agreement with the crosssection used in the simulations.…”
Section: Discussion a N D O U T L O O Kmentioning
confidence: 99%